Contingent Liability Risks from State-Owned Enterprises - World Bank (World Bank, Washington, DC, 2012)
Countries across all continents face the challenge of managing contingent liabilities arising from multiple sources, including state-owned enterprises (SOEs), parastatals, off-budget financing arrangements, civil servant entitlement schemes etc. The current financial crisis has made countries even more vulnerable to the severe impact of contingent liabilities on government finances, creating an urgent need to institutionalize systems to control and mitigate fiscal risks arising from these contingent liabilities. This note captures the technical advice provided by the Public Sector Performance (PSP) Global Expert Team (GET) in response to a just-in-time request by Bank staff working with government officials in a Middle-Eastern country to manage contingent liability risks arising from SOEs.